PARENTS' PERCEPTION OF THE QUALITY OF EDUCATION AT STATE ISLAMIC ELEMENTARY SCHOOL 4 WAY JEPARA, EAST LAMPUNG - Atika Vanya Salsabila; Nur Indah Sari; Apri Kurniasih (Al-Irsyad: Journal of Education Science, 2026)
This qualitative case study at Madrasah Ibtidaiyah Negeri 4 Way Jepara, East Lampung, investigates the perceptions of fifth-grade parents, focusing on cognitive, affective, and conative aspects, and the factors influencing these views. Motivated by a gap in comprehensive studies on parental perceptions in state madrasah ibtidaiyah in East Lampung, this research employed in-depth interviews, observation, and documentation with ten parent informants. Overall, the study revealed a highly positive parental perception, with a 75% positive response rate. Cognitively, parents recognize the madrasah's strength in integrating religious and general education. Affectively, they express satisfaction and trust in the institution. Conatively, parents fully support and actively recommend MIN 4 to others. Data analysis, using a thematic approach, identified internal influencing factors such as family religious values and high expectations for children's religious education. External factors included the madrasah's positive image, the quality of its teachers, and available facilities. These findings underscore the critical role of positive parental perceptions in bolstering madrasah education programs. The study concludes that continuous strengthening of communication strategies and improvement of educational service quality, aligning with parents' expectations, are crucial for the future growth and development of madrasas.